How Does The Educator's Character Influence Islamic Education? - Aulia Rahmania; Tyan Khoirunnissa; Dinar Ratna Sari (Universitas Muhammadiyah Surakarta, 2025)
This article examines how the character of educators affects Islamic education. This study is important because educators1 are examples for students. The character2 of the educator must be in accordance with what is taught in Islam, so that it does not become a conflict with students when the character of the educator deviates from what it should be. Teachers who are able to connect religious teachings with everyday life have great potential to influence students' mindsets and attitudes. This research method uses literature study research, which is a series of activities related to collecting library data, reading, analyzing and managing information obtained from various literacy sources . The results of the research obtained an explanation related to the concept of how the character of educators affects Islamic education3. The character of educators must be in accordance with Islamic teachings sourced from the Qur'an, Hadith, opinions of scholars and educational figures. It is hoped that future researchers can study and develop educators even better by adjusting to the development of information and communication technology or the times.